Transmission of Urogenital Schistosomiasis in Owena Reservoir Area, Ondo State Nigeria: Nexus Between Different Pathogenic Host Factors (American Journal of Life Science and Innovation, 2023)
A total of 25,482 snails, comprising 4,258 (16.7%) Bulinusglobosus; 213 (0.8%) Bulinustruncatus; 4,040 (15.9%) Bulinusforskalii; 4,770 (18.7%) Biomphalariapfeifferi; 6,024 (23.6%) Melanoidestuberculata; 1,730 (6.8%) Potadomafreethi; and 4,447 (17.5%) Pilaovata were collected over a period of 24 months during monthly site visits to Owena Reservoir Area which comprises of three communities namely Owena, Baiken and Kajola in Ondo East Local Government Area, Ondo State, Nigeria. The abundance of each of the snail species varied significantly (p